2015
DOI: 10.1294/jes.26.113
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of an extended photoperiod treatment on growth, gonadal function, and condition of hair coats in Thoroughbred yearlings reared under different climate conditions

Abstract: One- to two-year-old Thoroughbred colts and fillies being reared in Miyazaki (warm climate) and Hidaka (cold climate), Japan, were administered extended photoperiod (EP) treatment between December 20 and the following April 10, and its effect on growth, endocrine changes, gonadal activation, and hair coat condition was investigated. In colts reared in Miyazaki, no effect of EP treatment was noted on the growth indices, including body weight (BW), height at withers (HW), girth, and cannon circumference (CC), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…Regarding reproduction, the first ovarian activity designated by the levels of progesterone was obviously earlier in LS fillies from both Hokkaido and Miyazaki. The present results in conjunction with similar findings of previous studies [ 24 , 38 ] suggested that artificial light supplementation was able to stimulate prolactin secretion and the hypothalamic-pituitary-gonadal axis, resulting in enhancement of gonadal function and acceleration of growth in winter Hokkaido yearlings to levels similar to those of Miyazaki yearlings.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding reproduction, the first ovarian activity designated by the levels of progesterone was obviously earlier in LS fillies from both Hokkaido and Miyazaki. The present results in conjunction with similar findings of previous studies [ 24 , 38 ] suggested that artificial light supplementation was able to stimulate prolactin secretion and the hypothalamic-pituitary-gonadal axis, resulting in enhancement of gonadal function and acceleration of growth in winter Hokkaido yearlings to levels similar to those of Miyazaki yearlings.…”
Section: Discussionsupporting
confidence: 92%
“…The only important point concerning the measurement of estradiol by PATHFAST for use in the equine clinic is the detection limit of the assay. The range of the basal level of circulating estradiol during the estrous cycle [1,2,3,4,5] and the developmental stage [23,24,25,26,27] in mares is less than 20 pg/ml, and the detection limit of estradiol by PATHFAST is 20–2000 pg/ml. Extraction of serum by ether or other chemicals [28] will be required for measuring the basal estradiol level in mares using this estradiol PATHFAST.…”
mentioning
confidence: 99%
“…Extended photoperiod (EP) treatment activates the ovarian function earlier in broodmares, and it is widely used to advance the ovulation time in husbandry [ 15 ], because horses are typical long-day seasonal breeders. It has recently been reported that an EP treatment was applied to yearling horses and that it promoted growth rates, increased muscle mass, and advanced activation of gonadal function and coat molting [ 10 , 13 , 17 ]. The aim of the present study was to investigate whether EP treatment could successfully advance the annual molting pattern and gonadal function in Thoroughbred weanlings.…”
mentioning
confidence: 99%
“…The present study demonstrated for first time that EP treatment promotes the change from winter to summer coats (molting of winter coats) in weanlings. The EP treatment advanced early elevation of circulating progesterone in fillies, indicating that EP treatment also activates the gonadal function and ovulation in weanlings as well as broodmares and yearlings [ 10 , 13 , 15 , 17 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation